math help will.give brainliest
![math help willgive brainliest class=](https://us-static.z-dn.net/files/d25/dae2008826a775139d0776c97a7322e8.jpg)
Answer:
The point ( 0,-1) is a solution.
Step-by-step explanation:
y<= (x+1) (x+5)
y>= (x-1)^2 -6
See attached graph.
To prove algebraically, put the point (0,-1) into both equations and see if it is true for both of them.
y<= (x+1) (x+5)
-1 <= (0+1) (0+5)
-1<= 1*5
-1 <=5
True
y>= (x-1)^2 -6
-1 >= (-1)^2 -6
-1 >= 1-6
-1 >=-5
True
The point is a solution